Influence of the numbers of players in the heart rate responses of youth soccer players within 2 vs. 2, 3 vs. 3 and 4 vs. 4 small-sided games - Dellal, A.; Jannault, R.; Lopez-Segovia, M.; Pialoux, V. (Journal of Human Kinetics, 2011)
The purpose of this study was to compare heart rate (HR) responses within and between small-ided games (SSG) training methods in elite young soccer players. Twentyseven youth soccer players (age: 16.5+/-0.5 years, height: 174.5 +/-5.5 cm, weight: 62.9 +/-8.3, velocity at maximal aerobic speed (MAS): 15.9 +/-0.9 km/h) performed 3 different SSG (2 vs. 2, 3 vs. 3, 4 vs. 4 without goalkeeper). In each SSG, HR was continuously measured and expressed as a mean percentage of HR reserve (%HRreserve). The mean %HRreserve calculated during the SSG was significantly lower during 4 vs. 4 (70.6 +/-5.9 %) compared to 2 vs. 2 (80.1 +/-3.6 %, p<0.001) and 3 vs. 3 (81.5 +/-4.3 %, p<0.001) SSG. Regardless of the time spent above 60, 65, 70, 75, 80, 85 and 90 % of HRreserve, 4 vs. 4 solicited lower percentage of time than 3 vs. 3 and 2 vs. 2. Intersubject coefficients of variation were significantly higher during 4 vs. 4 compared to 2 vs.2 and 3 vs. 3. The %HRreserve after 30s of recovery was significantly higher for 3 vs. 3 (70.6 +/-5.3 %) compared to 2 vs. 2 (65.2 +/-4.8 %, p<0.05) and 4 vs. 4 (61.6 +/-9.3 %, p<0.05). In conclusion, this study demonstrates that the physiological demands is higher during 2 vs. 2 and 3 vs. 3 compared to 4 vs. 4 in youth soccer players. This difference could be due to that young soccer players do not have the same technical ability and experience as adult players and thus, their activity during the 2 vs. 2 and 3 vs. 3 induces a greater physical demand due to their lack of experience. The age of the players could be linked with the physical demands within small-sided games.